Impact of National Education Policy 2020 on Physical Education and Sports: A Comprehensive Review - Kapil Sharma; Sanjay Yadav (Recent Trends in Sports, 2025)
The Indian National Education Policy (NEP) 2020 is a historic project that aims to change the nation's educational system. The focus on improving sports and physical education in the classroom is one of its main elements. The importance of holistic education, where physical well-being is equally as significant as academic achievement, is acknowledged by this approach. NEP 2020 aims to make physical education a core part of the curriculum in order to support students' overall mental health, discipline, teamwork, and physical fitness. On a local and national level, it also creates structured sports programs to encourage participation. For children from diverse backgrounds, the approach encourages inclusive sports facilities, certified teachers, and modern infrastructure. It also highlights the significance of mental health, motivating pupils to use athletics to build resilience and coping mechanisms. It aims to eradicate current inequalities and establish a level playing field for all students by encouraging gender equity and equal opportunity in sports. Thus, in addition to improving kids' physical capabilities, the NEP helps them develop a strong sense of belonging and community. In addition, the NEP encourages collaboration between academic institutions, professional athletes, and sports academies in order to elevate sports as a legitimate career choice. This study looks at all of the NEP 2020 requirements, implementation strategies, challenges, and possible impacts on students and educational institutions that are related to sports and physical education.
Keywords: National Education Policy (NEP) 2020; holistic education; inclusive sports facilities; physical education; sports programs; student well-being